Combination Synchronization of Fractional Systems Involving the Caputo–Hadamard Derivative - Abdelhameed M. Nagy (MDPI AG, 2021)
The main aim of this paper is to investigate the combination synchronization phenomena of various fractional-order systems using the scaling matrix. For this purpose, the combination synchronization is performed by considering two drive systems and one response system. We show that the combination synchronization phenomenon is achieved theoretically. Moreover, numerical simulations are carried out to confirm and validate the obtained theoretical results.